2014
DOI: 10.1073/pnas.1407344111
|View full text |Cite
|
Sign up to set email alerts
|

Efficient utilization of complex N-linked glycans is a selective advantage for Bacteroides fragilis in extraintestinal infections

Abstract: Bacteroides fragilis is the most common anaerobe isolated from clinical infections, and in this report we demonstrate a characteristic of the species that is critical to their success as an opportunistic pathogen. Among the Bacteroides spp. in the gut, B. fragilis has the unique ability of efficiently harvesting complex N-linked glycans from the glycoproteins common to serum and serous fluid. This activity is mediated by an outer membrane protein complex designated as Don. Using the abundant serum glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 35 publications
2
68
0
Order By: Relevance
“…These data also indicate that Dps and DpsL may play overlapping roles in protecting the cells from oxidative stress damage in vivo, because the absence of both was required to see the phenotype. As previously shown in this model, B. fragilis reaches high cell numbers and then enters a stationary-like phase where the high cell density is maintained (8,31). Interestingly, on day 1 the ⌬dps ⌬bfr mutant was able to compete effectively with the wild type and was close to 50% of the 10 8 to 10 9 CFU/ml; however, on days 4 and 8, there was a decrease in the competitive ability of the double mutant (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…These data also indicate that Dps and DpsL may play overlapping roles in protecting the cells from oxidative stress damage in vivo, because the absence of both was required to see the phenotype. As previously shown in this model, B. fragilis reaches high cell numbers and then enters a stationary-like phase where the high cell density is maintained (8,31). Interestingly, on day 1 the ⌬dps ⌬bfr mutant was able to compete effectively with the wild type and was close to 50% of the 10 8 to 10 9 CFU/ml; however, on days 4 and 8, there was a decrease in the competitive ability of the double mutant (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Factors that contribute to B. fragilis survival within the abscess are poorly understood. In a previous study using the rat tissue cage model, in vivo microarray analysis demonstrated that the don locus was highly expressed in the infected tissue cages and was required for maximum survival in vivo (31). We reexamined these microarray data and found that there was a 4-to 6-fold increase in expression of dps and bfr, suggesting that Dps and DpsL may promote survival within the abscess.…”
Section: Fig 2 Dps Mediates Oxygen-induced Resistance To Tbooh (A) Omentioning
confidence: 77%
See 2 more Smart Citations
“…This can lead to peritonitis, intra-abdominal abscess, and bacteremia (9, 10). The dominance of B. fragilis in these infections can be attributed to an array of virulence factors that include polysaccharide capsule phase variation, a striking resistance to oxidative stress, and the ability to exploit novel host nutrient sources (11)(12)(13)(14).The ability to effectively compete for limited nutrients is essential for Bacteroides colonization in the gut as well as for success in extraintestinal infections. The key element of nutrient acquisition is the presence of a family of outer membrane protein complexes dedicated to the uptake and catabolism of polysaccharides (15)(16)(17).…”
mentioning
confidence: 99%